The COX-2/PGI2 receptor axis plays an obligatory role in mediating the cardioprotection conferred by the late phase of ischemic preconditioning. - Yiru Guo; Deepali Nivas Tukaye; Wen-Jian Wu; Xiaoping Zhu; Michael Book; Wei Tan; Steven P Jones; Gregg Rokosh; Shuh Narumiya; Qianhong Li; Roberto Bolli (PLoS ONE, 2012)
Pharmacologic studies with cyclooxygenase-2 (COX-2) inhibitors suggest that the late phase of ischemic preconditioning (PC) is mediated by COX-2. However, nonspecific effects of COX-2 inhibitors cannot be ruled out, and the selectivity of these inhibitors for COX-2 vs. COX-1 is only relative. Furthermore, the specific prostaglandin (PG) receptors responsible for the salubrious actions of COX-2-derived prostanoids remain unclear.To determine the role of COX-2 and prostacyclin receptor (IP) in late PC by gene deletion.COX-2 knockout (KO) mice (COX-2(-/-)), prostacyclin receptor KO (IP(-/-)) mice, and respective wildtype (WT, COX-2(+/+) and IP(+/+)) mice underwent sham surgery or PC with six 4-min coronary occlusion (O)/4-min R cycles 24 h before a 30-min O/24 h R.There were no significant differences in infarct size (IS) between non-preconditioned (non-PC) COX-2(+/+), COX-2(-/-), IP(+/+), and IP(-/-) mice, indicating that neither COX-2 nor IP modulates IS in the absence of PC. When COX-2(-/-) or IP(-/-) mice were preconditioned, IS was not reduced, indicating that the protection of late PC was completely abrogated by deletion of either the COX-2 or the IP gene. Administration of the IP selective antagonist, RO3244794 to C57BL6/J (B6) mice 30 min prior to the 30-min O had no effect on IS. When B6 mice were preconditioned 24 h prior to the 30-min O, IS was markedly reduced; however, the protection of late PC was completely abrogated by pretreatment of RO3244794.This is the first study to demonstrate that targeted disruption of the COX-2 gene completely abrogates the infarct-sparing effect of late PC, and that the IP, downstream of the COX-2/prostanoid pathway, is a key mediator of the late PC. These results provide unequivocal molecular genetic evidence for an essential role of the COX-2/PGI2 receptor axis in the cardioprotection afforded by the late PC.